Proceedings of the 5th International Conference on Physical Education, Sport, and Health (ACPES 2019) 2019
DOI: 10.2991/acpes-19.2019.32
|View full text |Cite
|
Sign up to set email alerts
|

Quality of U15 Gatra Semarang Badminton Club Players in 2019

Abstract: Gatra Semarang Badminton Club players at low achievement are suspected of having quality problems. This research is to describe the technical and physical quality of them. This research is a quantitative study with descriptive results. The population as well as the research sample of nine male players housed under the age of 15 years. This research variable is the quality of Gatra Semarang Badminton Club in 2019. Retrieval of data using technical instruments (clear service, lop, smash and drop shot) and physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This study identified and quantified minerals and vitamins in purple sweet potato leaf flour that can provide health benefits, being a good source of nutrition. Previous research has found minerals (K, Na, Ca, µg, Cu, Zn, Fe, and Mn) in purple sweet potato leaves [30]. In addition, previous research also found the fact that purple sweet potato leaves contained minerals (Fe, Zn, Cu, Mn, Ca, K, µg, Na, P, and Vitamin C and Betacarotene [7].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This study identified and quantified minerals and vitamins in purple sweet potato leaf flour that can provide health benefits, being a good source of nutrition. Previous research has found minerals (K, Na, Ca, µg, Cu, Zn, Fe, and Mn) in purple sweet potato leaves [30]. In addition, previous research also found the fact that purple sweet potato leaves contained minerals (Fe, Zn, Cu, Mn, Ca, K, µg, Na, P, and Vitamin C and Betacarotene [7].…”
Section: Discussionmentioning
confidence: 92%
“…In addition, copper supports the function of blood vessels, the nervous system, and the immune system, as well as bone growth [29]. The copper content of these purple sweet potato leaves (is 5 µg/100g), while the copper requirement for children and adults is 1-3 µg/day [6], and for pregnant and lactating women 50 -120 µg/day [30].…”
Section: Mineral Contentmentioning
confidence: 99%
See 1 more Smart Citation